Fertigation via Center Pivot Irrigation for Commercial Potato Production in Florida - Guodong Liu; Xiangju Fu; Lincoln Zotarelli; Steven Sargent; Kati Migliaccio; Yuncong Li (EDIS, 2020)
Potatoes are an important crop in the United States, and Florida is ranked the 7th producer nationwide for potato production. In Florida, potatoes are mainly planted on sandy soils with low nutrient- and water-holding capacities. Nitrogen is the most limiting nutrient in these soils. Adopting efficient fertilization methods such as fertigation is imperative for minimizing leaching and improving use efficiency of nitrogen. This new 12-page article provides step-by-step guidelines for fertigation practices for commercial potato production. Written by Xiangju Fu, Guodong Liu, Lincoln Zotarelli, Steven Sargent, Kati Migliaccio, and Yuncong Li, and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1361